Caloric restriction protects against electrical kindling of the amygdala by inhibiting the mTOR signaling pathway - Phillips-Farfán, Bryan V.; Rubio Osornio, María del Carmen; Custodio Ramírez, Verónica; Paz Tres, Carlos; Carvajal Aguilera, Karla G. (Frontiers in Cellular Neuroscience, 2015)
Caloric restriction (CR) has been shown to possess antiepileptic properties; however its mechanism of action is poorly understood. CR might inhibit the activity of the mammalian or mechanistic target of rapamycin (mTOR) signaling cascade, which seems to participate crucially in the generation of epilepsy. Thus, we investigated the effect of CR on the mTOR pathway and whether CR modified epilepsy generation due to electrical amygdala kindling. The former was studied by analyzing the phosphorylation of adenosine monophosphate-activated protein kinase, protein kinase B and the ribosomal protein S6. The mTOR cascade is regulated by energy and by insulin levels, both of which may be changed by CR; thus we investigated if CR altered the levels of energy substrates in the blood or the level of insulin in plasma. Finally, we studied if CR modified the expression of genes that encode proteins participating in the mTOR pathway. CR increased the after-discharge threshold and tended to reduce the after-discharge duration, indicating an anti-convulsive action. CR diminished the phosphorylation of protein kinase B and ribosomal protein S6, suggesting an inhibition of the mTOR cascade. However, CR did not change glucose, β-hydroxybutyrate or insulin levels; thus the effects of CR were independent from them. Interestingly, CR also did not modify the expression of any investigated gene. The results suggest that the anti-epileptic effect of CR may be partly due to inhibition of the mTOR pathway.